Caractéristiques Structurales Des Peuplements Ligneux À Syzygium Guineense (Willd.) DC. Subsp. Macrocarpum (Myrtaceae) En Vue De Leur Aménagement À Des Fins Apicoles Au Bénin - Badou Badjrêhou Romaël; Yedomonhan Hounnankpon (European Scientific Journal, ESJ, 2017)
The potential of honey production by honeybee in one area are determined by the flora. This study aims to evaluate the structural characteristics of Syzygium guineense subsp. macrocarpum so as to propose its promotion for beekeeping in Benin. Some structural variables were collected through 18 plots of one hectare (100 m x 100 m). It was installed at random in three classified forests in sudano-guinean zone. Each plot was divided into 16 plots of 625 m² (25m x 25m). For all species of tree and shrub, the stems of dbh ≥ 10 cm have the highest values of density (549 stems/ha) and landed surface (14.06 m2/ha) in dry dense forest. However, their middle height (17.53 m) and their middle diameter (22.96 cm) are more raised in wood land savanna. In regards to exclusive stems of S. guineense subsp. macrocarpum, their high values of density (6 stems/ha), landed surface (0.30 m2/ha), and middle diameter (17.84 cm) were recorded in the dry dense forest. The relative contribution of S. guineense subsp. macrocarpum to woody population density varied between 0.45 and 1.04% for wood or shrub of dbh ≥ 10 cm. It also varies between 0.16 and 0.28% for wood or shrub of dbh< 10 cm. The abundance index ranged from 0.09 to 0.77 and from 0.21 to 0.39 respectively for individual of dbh ≥ 10 cm dbh and < 10 cm. The weak values of seedling density require an assessment of its fructiferous production.